The pillars of the earth ebook - Follett, Ken (Kingsbridge, 2010)
#1 New York Times Bestseller Oprah's Book Club Selection The “extraordinary . . . monumental masterpiece” ( Booklist ) that changed the course of Ken Follett’s already phenomenal career—and begins where its prequel,  The Evening and the Morning , ended. “Follett risks all and comes out a clear winner,” extolled  Publishers Weekly  on the release of  The Pillars of the Earth . A departure for the bestselling thriller writer, the historical epic stunned readers and critics alike with its ambitious scope and gripping humanity. Today, it stands as a testament to Follett’s unassailable command of the written word and to his universal appeal.    The Pillars of the Earth  tells the story of Philip, prior of Kingsbridge, a devout and resourceful monk driven to build the greatest Gothic cathedral the world has known . . . of Tom, the mason who becomes his architect—a man divided in his soul . . . of the beautiful, elusive Lady Aliena, haunted by a secret shame . . . and of a struggle between good and evil that will turn church against state and brother against brother.   A spellbinding epic tale of ambition, anarchy, and absolute power set against the sprawling medieval canvas of twelfth-century England, this is Ken Follett’s historical masterpiece.